Factors associated with prognosis of upper limb function in branch atheromatous disease - Tokuda, Kazuhiro; Hanada, Keisuke; Takebayashi, Takashi; Koyama, Takashi; Fujita, Toshiaki; Okita, Yuho (Clinical neurology and neurosurgery, 2022)
Branch atheromatous disease (BAD) is often associated with corticospinal tract injury, and some patients develop early neurological deterioration (END) in the acute phase. This study investigated the progress of upper limb prognosis after BAD in the acute phases and examined the factors related to the prognosis of upper limb function. Procedures: 108 subjects diagnosed with BAD were included. Then subjects were classified into two groups: those with good recovery of upper limb function and those with poor recovery of upper limb function. Univariate and multivariate analyses were performed with the objective variable being good or poor upper limb function. The following factors were used as explanatory variables: age, the volume of infarction, initial Fugl-Meyer assessment (FMA) upper limb score, and presence of END. Main findings: The univariate analysis showed significant differences in age and volume of infarction (p < 0.05). Multivariate analysis showed the following finding: age;(OR 0.977,95%CI 0.917–0.997,p = 0.0061; volume of infarction;(OR 0.645,95%CI 0.461–0.902,p = 0.0104). A significant difference was found in the age and volume of the infarct. Conclusion: This study finding suggests that age and volume of infarction are associated with the prognosis of upper extremity paralysis in BAD. •This study used logistic regression analysis to extract factors associated with the prognosis of upper extremity function in BAD.•The results showed that the prognosis of upper extremity function after BAD was related to the age and volume of the infarction.•This study highlights thean importance of providing rehabilitation of upper limb paralysis in BAD early in the acute phase regardless of neurological changes.